Coal, oil and gas going into extra time: The narrative of abated fossil fuels threatens to undermine the Paris climate targets - Gerrit Hansen (Stiftung Wissenschaft und Politik (SWP), 2023)
The upcoming United Nations Climate Change Conference in Dubai (COP28) will see a new round of battle regarding the call to phase out fossil fuels. Intense debates have taken place in Germany and the European Union (EU) to determine positions in the run-up to the conference. The main point of contention is whether to call for a complete global phase-out of all fossil fuels or only for a phase-down of their unabated use, that is, without additional abatement measures such as carbon capture and storage (CCS). The role of abated fossil fuels in a net-zero economy is very controversial. In the long run, it will depend on several factors, including the effective deployment and scale-up of CCS, the capture rates achieved therein and the availability of carbon dioxide removal (CDR) technologies to address residual emissions. CCS is unlikely to make a significant contribution to urgently needed greenhouse gas reductions in the power sector by 2030. Whether the decision in Dubai will deliver a credible signal to rapidly reduce fossil fuel emissions depends in no small part on a precise, science-based definition of the scale of emission reductions required for fossil fuels to be considered as abated in line with the temperature goal of the Paris Agreement.
Keywords: 320; United Nations Climate Change Conference in Dubai 2023 (COP28); Intergovernmental Panel on Climate Change (IPCC); global CO2 emissions; net zero; climate crisis; European Union (EU); Carbon Capture and Storage (CCS); Carbon Dioxide Removal (CDR); UNFCCC; coal; oil; gas; Global Stocktake (GST)